Reduced IL-17A levels in neonates born to mothers with diabetes mellitus or infection during pregnancy - Li, Tingting; Hu, Sufen; Guo, Fangfang; He, Youming; Cheng, Haiping; Wu, Mengying; Mao, Yan; Zhang, Kexin; Lin, Juan; Li, Rui; Ma, Defei; Li, Shiting; et al. (Frontiers in Pediatrics, 2025)
Background/ObjectivesPregnancy complications are associated with adverse maternal–neonatal outcomes, but the underlying immune mechanisms remain unclear. Here we examined umbilical cord IL-17A levels and their link to gestational diabetes mellitus (GDM) and perinatal infections (PIs).MethodsThis two-phase study analyzed 87 pregnant women (38 in the exploratory phase and 49 in the validation phase) from Shenzhen's Premature Infants Gut Microbiota Assembly and Neurodevelopment (PIGMAN) cohort, divided into perinatal complication (PC) (45 cases) and non-perinatal complication (NPC) (42 cases) groups. Cord blood IL-17A levels were measured by ELISA and analyzed as a continuous variable by Nonparametric rank-sum test and a categorical variable using Fisher's exact test.ResultsNonparametric analysis revealed consistently lower IL-17A levels in the PC group across both phases. The discovery phase median in the PC group was 0.67 pg/ml lower than the 5.68 pg/ml median in the NPC group (p = 0.001); in the validation phase, the PC and NPC group levels were 0.93 and 2.05 pg/ml (p = 0.012), respectively. Low IL-17A (<1 pg/ml) prevalence was significantly higher in PC cases (discovery: 61.9% vs. 11.8%, p = 0.002; validation: 50% vs. 36%, p = 0.031). Rank-sum test and Fisher's exact test demonstrated concordant results, confirming a robust association between reduced IL-17A levels and perinatal complications.ConclusionUmbilical cord blood from PC pregnancies exhibited significantly lower IL-17A levels compared to that from NPC pregnancies, suggesting compromised neonatal cellular immunity. These findings implicate IL-17A deficiency in the immune dysregulation associated with GDM and PI. Conversely, the higher IL-17A levels observed in NPC pregnancies may reflect its protective role in maternal–fetal immunity during early development.